A radiation-hard PLL for frequency multiplication with programmable input clock and phase-selectable output signals in 130 nm CMOS - Poltorak, K; Tavernier, F; Moreira, P (Journal of instrumentation, 2012)
A PLL (ePLL) is presented that is intended to be used as a frequency multiplier. The ePLL accepts 40, 80, 160 or 320 MHz as a reference and generates clocks at the same frequencies, regardless of the input clock. Moreover, the outputs are available with a phase resolution of 90 degree for the 40, 80 and 160 MHz output and 22.5 degree for the 320 MHz output. The radiation-hard design, integrated in a 130 nm CMOS technology, is able to operate at a supply voltage between 1.2 V and 1.5 V.